Overview of the Therapeutic Applications of Stem Cell–Derived Exosomes: A Research and Commercial Perspective. Issue 9 (7th September 2021) - Heale, Kali A.; Nath, Suman C.; Rancourt, Derrick E.
Abstract: Progress in extracellular vesicle (EV) research over the past two decades has generated significant interest in using EVs in the biomedical field. Exosomes are a subgroup of EVs that comprise endocytic membrane‐bound nanovesicles of 40 to 160 nm diameter. These vesicles have been shown to facilitate intercellular communication via the delivery of cellular molecules. There are currently several exciting applications for exosomes being developed in therapeutics, diagnostics, drug delivery, and cellular reprogramming. Stem cell–derived exosomes present the opportunity to harness the power of stem cells while circumventing several of the risks associated with their use. This review summarizes the recent developments in exosome technology and lends a prospective view to the future of exosome use and application in research and medicine. Through a review of relevant patent filings, recent literature, and ongoing clinical trials, a valuable overview of the field of exosomes is provided. © 2021 Wiley Periodicals LLC.